(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The growth of electronic retailing has intensified competition among online retailers, making effective order fulfillment an essential factor for sustaining customer relationships. This study examined the relationship between order fulfillment and customer retention among e-tail outlets in Yenagoa, Bayelsa State, Nigeria. Specifically, the study investigated how order accuracy and delivery timeliness influence customer satisfaction and repeat purchase behavior. The study adopted a cross-sectional research design and utilized a structured questionnaire to collect primary data from customers of selected e-tail outlets. Using the Taro Yamane formula, a sample size of 400 respondents was determined, while 110 valid responses were used for the final analysis. Data were analyzed using descriptive statistics and Spearman’s rank-order correlation coefficient with the aid of SPSS version 25. The findings revealed that order accuracy has a strong and significant relationship with customer satisfaction (r = 0.814, p < 0.01) and a significant relationship with repeat purchase (r = 0.574, p < 0.01). The results also showed that delivery timeliness has a very strong and significant relationship with customer satisfaction (r = 0.961, p < 0.01) and repeat purchase behavior (r = 0.931, p < 0.01). These findings indicate that efficient order fulfillment practices play a critical role in enhancing customer satisfaction and encouraging repeat patronage among e-tail customers. The study concludes that order fulfillment dimensions, particularly order accuracy and delivery timeliness, significantly influence customer retention in e-tail operations. It therefore recommends that e-tail outlets invest in improved inventory management systems, reliable delivery networks, and effective logistics coordination to enhance service efficiency and customer loyalty.